2011
DOI: 10.2478/s11535-011-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of mineral nutrients and sugars throughout the lifespan of Hibiscus rosa-sinensis L. flower

Abstract: Although the physiological and molecular mechanisms of flower development and senescence have been extensively investigated, a whole-flower partitioning study of mineral concentrations has not been carried out. In this work, the distribution of sucrose, total reducing sugars, dry and fresh weight and macro and micronutrients were analysed in Hibiscus rosa-sinensis L. petals, stylestigma including stamens and ovary at different developmental stages (bud, open and senescent flowers). Total reducing sugars showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Seven transcripts encoding autophagy genes ( ATG8c , ATG8f , and ATGg ; Supplementary Table S15) were strongly induced in senescing petals and S-S+S tissues. During hibiscus flower senescence, the nitrogen, phosphorus, potassium, and micro-nutrient content of petals and S-S+S is significantly reduced, supporting a possible role of autophagy in the degradation and remobilization of macromolecules during flower ageing (Trivellini et al , 2011 c ). These data support the previously documented role for autophagy in petal senescence (Yamada et al , 2009; Shibuya et al , 2013), pointing out also its role in senescing S-S+S as a major nutrient recycling mechanism in plants as suggested by Coll et al (2014).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Seven transcripts encoding autophagy genes ( ATG8c , ATG8f , and ATGg ; Supplementary Table S15) were strongly induced in senescing petals and S-S+S tissues. During hibiscus flower senescence, the nitrogen, phosphorus, potassium, and micro-nutrient content of petals and S-S+S is significantly reduced, supporting a possible role of autophagy in the degradation and remobilization of macromolecules during flower ageing (Trivellini et al , 2011 c ). These data support the previously documented role for autophagy in petal senescence (Yamada et al , 2009; Shibuya et al , 2013), pointing out also its role in senescing S-S+S as a major nutrient recycling mechanism in plants as suggested by Coll et al (2014).…”
Section: Resultsmentioning
confidence: 93%
“…This condition might be supported by the considerable differential regulation of aquaporin gene expression among different flower developmental stages. In hibiscus, it has been shown that flower senescence entrains circadian rhythms via endogenous oscillations in sugars (Trivellini et al , 2011 c ). This opens the possibility that variation in sugar may be important in entrainment of the clock in the flower petals and regulation of aquaporins.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the nutrient profiles of senescing Hibiscus rosa-sinensis (hibiscus) are very similar to the pollination-induced changes in petunia corollas (Chapin and Jones 2007; Trivellini et al 2011). Hibiscus is an ethylene-sensitive, ephemeral flower that opens and wilts within 1 day.…”
Section: Nutrient Remobilization During Petal Senescencementioning
confidence: 86%
“…The senescence of ephemeral flowers is generally not accelerated by pollination. Nutrient remobilization studies indicate that the senescence of these flowers may be more similar to pollination-induced senescence than developmental senescence in their longer-lived counterparts (Winkenbach 1970; Trivellini et al 2011). In Japanese morning glories, petal senescence starts before the flowers are even open (Winkenbach 1970).…”
Section: Nutrient Remobilization During Petal Senescencementioning
confidence: 99%
See 1 more Smart Citation